Nonverbal Communication in Journalism: A Literature Review on the Meet Nite live Broadcast on Metro TV - Maria Septian Riasanti Mola (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2025)
This literature review explores the role of nonverbal communication in the context of television journalism, particularly in the Meet nite live program broadcast by Metro TV. In television news delivery, communication is not solely reliant on verbal elements but is significantly supported by nonverbal cues such as facial expressions, gestures, eye contact, vocal intonation, and spatial use. Drawing from established theories of nonverbal communication and journalism studies, this paper examines how such nonverbal elements contribute to message construction, audience perception, and the credibility of presenters. The findings highlight that nonverbal communication in journalistic broadcasts serves not only to support verbal content but also to convey attitudes, manage impressions, and regulate interactions within the studio setting. This review aims to provide theoretical insights for future empirical research and offers recommendations for journalists and media practitioners to enhance the effectiveness and professionalism of news presentation.